High-frequency in vitro propagation of the endangered species Tuberaria major - Gonçalves, Sandra (2013)
A novel protocol suitable for the micropropagation of the endangered species Tuberaria major using seedlings as explants is reported. Using this protocol, we studied the effects of explant type (apical shoots and nodal segments) and cytokinins [6-benzyladenine (BA), kinetin,and zeatin (ZEA)] on shoot proliferation. Explant type significantly influenced the proliferation frequency and mean number of shoots, with nodal segments showing a higher proliferation capacity. The mean number of shoots was significantly higher when the explants were cultured in half-strength (1/2) MS medium supplemented with 0.2 mg l-1 BA (6.83 ± 0.77 shoots) or ZEA (6.55 ± 0.71 shoots). The shoots showed a great rooting capacity that was significantly influenced by the concentration of MS macronutrients but not by the concentration of auxins. The highest rooting frequencies (97–100%) were obtained in 1/2 MS medium with or without plant growth regulators. The plants obtained were easily acclimatized to ex vitro conditions, with 97% surviving after 6 weeks. The micropropagated plants were successfully reintroduced into their natural habitat and exhibited normal development. In conclusion, our culture protocol, with efficient seed germination, subsequent multiplication of nodal explants using ZEA at 0.2 mg l-1, and successful ex vitro establishment of well-rooted plantlets on 1/2 MS medium, provides a simple and reliable methodology for the large scale propagation of T. major, thereby contributing to germplasm preservation of this endangered species.